Phosphate Adsorption Capacity of Allophane from Two Volcanic Mountains in Indonesia - Tandaditya Ariefandra Airlangga; Naoto Matsue; Eko Hanudin; Erni Johan (JOURNAL OF TROPICAL SOILS, 2020)
Allophane is known as clay mineral with high capacity of phosphate adsorption via ligand-exchange mechanism. This study aims to compare the phosphate adsorption characteristics by allophane from Mt. Merapi and Mt. Lawu in relation to its chemical and mineralogical properties. The results  of X-Ray Flourescence analysis shows that both allophane samples from Merapi and Lawu have low Si/Al ratio, i.e. 1.18 and 1.16, respectively. Infrared spectral characteristics of the allophane materials indicated that the main adsorption bands appeared at the range of 2700-3700 cm-1 (due to stretching vibration of all hydroxyl (OH) groups), 1400 – 1800 cm-1 (vibration of HOH deformation), and 650 - 1200 cm-1 (vibration between the Si-O-Al). Adsorption experiment of phosphate on allophane samples were conducted at initial adsorbate concentration of up to 2.0 mM and at pH 4.0 and 8.0. Phosphate adsorption capacity of allophane shows that both allophane from Merapi and Lawu are categorized as very high in adsorbing phosphate and fit well with the Langmuir adsorption equation. Phosphate adsorption increases with decreasing pH due to the positive charge sites such as Al-OH2+ in the allophane structure increase. Another reason is the negative charge of phosphate gradually decreases from -2 to -1 with decreasing pH, and the repulsive force between the negatively charged Si-O- in the allophane structure and phosphate anions decreases.